Perancangan Sistem Kontrol dan Monitoring Kualitas Air dan Suhu Air Pada Kolam Budidaya Ikan - Pramana, Rozeff (Fakultas Teknik Universitas Maritim Raja Ali Haji, 2018)
The quality and the temperature of pond water is an important parameter that need to get attention in fish cultivation. Every type of fish has their own characteristic towards water condition and pond temperature.  The monitoring of water quality in cultivation pond is done manually and it takes a lot of time. The purpose of this research is to design web-based control system device and monitoring the quality of the water of fish cultivation pond including salinity, temperature and the hardness in real time using special application. This device design consists of salinity sensor, hardness sensor, and temperature sensor. Temperature can be controlled and monitored automatically on the application via computer/laptop. The result of this research is temperature drop by 0,1 oC on a 10 liters pond that takes 18 seconds, and to decrease the temperature of 1 oC takes 180 seconds (3 minutes). To raise the temperature of 0,1 oC takes 264 seconds or 4,4 minutes, and to raise the temperature of  1 oC takes 2640 seconds or 44 minutes. The percentage of error for sensor reading is ranged 2,4% - 3,9%.